The No-Report Paradigm: A Revolution in Consciousness Research? - Duman, Irem; Ehmann, Isabell Sophia; Gonsalves, Alicia Ronnie; Gültekin, Zeynep; Van den Berckt, Jonathan; van Leeuwen, Cees (Frontiers in Human Neuroscience, 2022)
In the cognitive neuroscience of consciousness, participants have commonly been instructed to report their conscious content. This, it was claimed, risks confounding the neural correlates of consciousness (NCC) with their preconditions, i.e. allocation of attention, and consequences, i.e. metacognitive reflection. Recently, the field has therefore been shifting towards no-report paradigms. No-report paradigms draw their validity from a direct comparison with no-report conditions. We analyze several examples of such comparisons and identify alternative interpretations of their results and/or methodological issues in all cases. These go beyond the previous criticism that just removing the report is insufficient, because it does not prevent metacognitive reflection. The conscious mind is fickle. Without having much to do, it will turn inward and switch, or time share, between the stimuli on display and daydreaming or mind-wandering. Thus, rather than the NCC, no report paradigms might be addressing the neural correlates of conscious disengagement. This observation reaffirms the conclusion that no-report paradigms are no less problematic than report paradigms.